PENGARUH TINGKAT PENDIDIKAN FORMAL DAN PEMAHAMAN AGAMA ISLAM ORANG TUA TERHADAP KECERDASAN SPIRITUAL ANAK DI DESA TANJUNG AGUNG KECAMATAN SEGINIM - Deko Rio Putra (IAIN Bengkulu, 2016)
This research aims to: (1) the effect of formal education levels of parents of spiritual intelligence of children in the village of Tanjung Agung, (2) the effect of the understanding of Islam parent to spiritual intelligence of children in the village of Tanjung Agung, (3) the effect of educational level formal and understanding of the Islamic religion to the intelligence of the spiritual parents of children in the village of Tanjung Agung. Research variables are considered: (1) the independent variable (X11) is the formal education level of parents, (2) the independent variable (X12) which is understanding Islam parents, (3) the dependent variable (Y) that is spiritual intelligence of children in the village of Tanjung Agung. The results of the analysis of these data is a positive relationship between the effect of formal education levels of parents of spiritual intelligence of children in the village of Tanjung Agung, according to the statistical hypothesis proposed Ho: y1 < 0, Ha: y1> 0, because the price of greater than 0 ( 0,146> 0), it can be concluded there is a positive and significant relationship between the effect of 0,146 formal education levels of parents of spiritual intelligence of children in the village of Tanjung Agung. As for the influence of the understanding of Islam parent to spiritual intelligence of children in the village of Tanjung Agung is a positive relationship, according to the statistical hypothesis proposed Ho: y2 < 0, Ha: y2 > 0, because the price of greater than 0 (0.717 > 0) , it can be concluded there is a positive and significant correlation of 0.717 between the influence of Islamic religious understanding of parents of spiritual intelligence of children in the village of Tanjung Agung. The results of the regression analysis contained significant influence between the level of formal education and understanding of the Islamic religion to the spiritual intelligence of parents of children in the village of Tanjung Agung based on the calculated value F is greater than the value of table F, that of F = 16.95 and Ftabel = 3, 35, so that the calculated value F is the rejection region of Ho. To contribute jointly (simultaneously) variables X1 and X2 to Y is 0.524 or (RX1Y, X2Y = 0.524). Because the value of r count> 0 or 0.524> 0, so Ha is received. It can be concluded there is a positive and significant correlation of 0.524. Thus the researchers suggested that the Spiritual Intelligence was associated with the level of formal education and understanding of Islam parents. for the good and the least spiritual intelligence of the child depends on the level of formal education and understanding of Islam parents